Immunobiotic Lactobacillus jensenii Elicits anti-inflammatory activity in porcine intestinal epithelial cells by modulating negative regulators of the toll-like receptor signaling pathway - Shimazu, Tomoyuki (2012)
The effect of Lactobacillus jensenii TL2937 on the inflammatory immune response triggered by enterotoxigenic Escherichia coli (ETEC) and lipopolysaccharide (LPS) in a porcine intestinal epitheliocyte cell line (PIE cells) was evaluated. Challenges with ETEC or LPS elicited toll-like receptor (TLR)-4-mediated inflammatory responses in cultured PIE cells, indicating that our cell line may be useful for studying inflammation in the guts of weaning piglets. In addition, we demonstrated that L. jensenii TL2937 attenuated the expression of pro-inflammatory cytokines and chemokines caused by ETEC or LPS challenge by downregulating TLR4-dependent nuclear factor-κB (NF-κB) and mitogen-activated protein kinase (MAPK) activation. Furthermore, we demonstrated that L. jensenii TL2937 stimulation of PIE cells upregulated three negative regulators of TLRs: A20, Bcl-3 and MPK-1, deepening the understanding of an immunobiotic mechanism of action. L. jensenii TL2937-mediated induction of negative regulators of TLRs would have a substantial physiological impact on homeostasis in PIE cells because excessive TLR inflammatory signaling would be downregulated. These results indicated that PIE cells can be used to study the mechanisms involved in the protective activity of immunobiotics against intestinal inflammatory damage and may provide useful information for the development of new immunologically functional feeds that help to prevent inflammatory intestinal disorders, including weaning-associated intestinal inflammation.